2021
DOI: 10.5380/ce.v26i0.78275
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Vida Dos Profissionais De Saúde Pós-Covid-19: Um Estudo Transversal

Abstract: Objetivo: avaliar a qualidade de vida de profissionais de saúde testados para covid-19 em uma policlínica no estado do Rio de Janeiro.Método: estudo transversal com 476 profissionais de saúde, que realizaram teste para a detecção da covid-19 nos meses de março a julho de 2020. Aplicou-se questionário sociodemográfico e de qualidade de vida da Organização Mundial de Saúde. As pontuações de cada domínio foram transformadas numa escala de 0-100; as médias mais altas sugerem melhor percepção da qualidade de vida.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Our first aim was to describe QoL, HRQoL, and functioning in a large sample of people with PCC with different COVID‐19 severities and compare these data with those from healthy control participants. Very few studies have examined QoL in individuals post‐COVID‐19, 59 with the majority of them primarily focusing on health care workers 60,61 . When testing QoL using the WHOQoL‐BREF, we found that participants with PCC scored lower than HCs on a subset of QoL measures that address physical and mental health.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our first aim was to describe QoL, HRQoL, and functioning in a large sample of people with PCC with different COVID‐19 severities and compare these data with those from healthy control participants. Very few studies have examined QoL in individuals post‐COVID‐19, 59 with the majority of them primarily focusing on health care workers 60,61 . When testing QoL using the WHOQoL‐BREF, we found that participants with PCC scored lower than HCs on a subset of QoL measures that address physical and mental health.…”
Section: Discussionmentioning
confidence: 86%
“…Very few studies have examined QoL in individuals post-COVID-19, 59 with the majority of them primarily focusing on health care workers. 60,61 When testing QoL using the WHOQoL-BREF, we found that participants with PCC scored lower than HCs on a subset of QoL measures that address physical and mental health. Moreover, we found that participants who had mild COVID-19 reported worse QoL than those who were admitted to an ICU.…”
Section: Discussionmentioning
confidence: 90%
“…O pior desempenho em domínio ambiental corrobora com dados da literatura, trazendo uma maior robustez de que a pandemia influenciou negativamente na QV de profissionais da saúde, principalmente no que tange as questões relacionadas ao ambiente, percepção de segurança e bem-estar [15,16].…”
Section: Discussionunclassified
“…Além disso, a qualidade de vida dos profissionais de saúde foram comprometidas, principalmente, aqueles que tiveram infecção pelo vírus, foi identificado que os domínios físico, psicológico, relações sociais e meio ambiente foram comprometidos. Sendo que o mais afetado foi o meio ambiente que tem relação com o ambiente em que vive, finanças, lazer e o físico foi o domínio menos comprometido, que está atrelado a dor e capacidade física de exercer as atividade (PIRES BMFB, et al, 2021).…”
Section: Introductionunclassified